(untitled) (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2023)
This study aims to describe and explain: (1) the prose structure in Sêrat Kabar Angin; (2) personality aspects of the characters in Sêrat Kabar Angin; and (3) the character education value of Sêrat Kabar Angin. This research method is descriptive qualitative through a literary psychology approach. This type of research is library research. The data source is the manuscript of Sêrat Kabar Angin by Ki Padmasusastra. The primary data is the text of Sêrat Kabar Angin by Ki Padmasusastra. Supporting data are books and research journals that are relevant for reference. Data collection techniques with content analysis. Data validity uses theoretical triangulation. Data analysis techniques include data reduction, data presentation, drawing conclusions and data verification. The results of the study are as follows: (1) the prose structure shows a unified whole from the elements of theme, plot, character, setting, and point of view, which are interrelated with one another; (2) aspects of the character’s personality are revealed by Sigmund Freud’s theory which shows that the superego acts as an obstacle to the id and ego of each character in the story, and the superego is based on the results of education, morality, and the values prevailing in society; and (3) the value of Sêrat Kabar Angin’s character education includes the value of character education related to God, namely religiosity; the values of character education relating to oneself, namely: honesty, responsibility, hard work, independence, and entrepreneurial spirit; the values of character education that are related to each other, namely adherence to social regulations, respect for the work and achievements of others, and politeness; the value of character education related to the environment, namely social care; and the value of character education related to national values, namely the value of nationalism character education.